OPTIMALISASI PERAN KEPALA SEKOLAH DALAM PENGEMBANGAN PROFESSIONAL LEARNING COMMUNITY UNTUK DEEP LEARNING - Mumuh, Mumuh; Ali, Rohendi; Rosmaladewi, Okke (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to identify and describe the role of school principals in the development of the Professional Learning Community (PLC), analyze the challenges faced by principals in implementing PLC to support deep learning, and formulate recommendations for best practices for principals in creating a collaborative learning environment. The method used in this study is a qualitative approach, involving in-depth interviews with school principals and observations in several schools that have implemented PLC. The results show that school principals have a central role in developing PLC through inspiring leadership and support for collaboration among teachers. However, the challenges faced include resistance from staff, lack of understanding of the PLC concept, and resource limitations. Based on these findings, best practice recommendations were formulated to help school principals, including: improving training and professional development for staff, encouraging open and collaborative communication among teachers, and providing adequate resources to support PLC implementation. The implications of this research are expected to provide guidance for school principals in creating and managing a collaborative and effective learning environment.